Mediasi Sebagai Alternatif Penyelesaian Sengketa Waris Untuk Meminimalisir Penumpukan Sengketa di Pengadilan Agama - Angel May Marta Naftalia; Mega Dwi Ambarwati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The division of inheritance does not always run smoothly. Many disputes occur between the heirs, both before and after the distribution of the inheritance. Disputes can be resolved by mediation, either out of court (non-litigation) or in court (litigation). Settlement of disputes over the division of inheritance by way of mediation is an alternative that can create a harmonious family atmosphere. Inheritance disputes can be resolved by mediation in court (litigation) because inheritance disputes are the absolute authority of the Religious Court. There is still a large amount of backlog or backlog of disputes in court through the general judiciary, this is not in accordance with the principles of fast, simple and low-cost justice. If this principle has not been implemented properly, it will have an impact on the accumulation of disputes in Court. So there is a need for alternative dispute resolution that can minimize the buildup of disputes in court. The importance of this discussion is to provide an understanding that settlements cannot only be resolved through court, but can also be resolved outside of court in order to minimize the buildup of disputes in court. This research was studied using studies normative law, qualitative research specifications, secondary data sources and using qualitative data analysis. Mediation as an alternative in dispute resolution is very effective in reducing the buildup of disputes in court. Mediation is a solution that ensures that the winning party does not feel like they have won and the losing party does not feel like the losing party. So mediation prioritizes a win-win solution for the parties.